HUBUNGAN ANTARA KELELAHAN KERJA DENGAN NYERI MUSCULOSKELETAL DISORDERS PADA PEKERJA PABRIK TAHU JAKARTA TIMUR - Rut Grasela Sibarani (2023)
Background: Musculoskeletal complaints are usually caused by excessive muscle contractions as a result of burdensome workloads in the long term. Musculoskeletal disorders have a relationship with work fatigue depending on the severity. The negative impact of work fatigue is significant on productivity, concentration, mood, alertness, problem-solving skills and work performance. One of the jobs that causes musculoskeletal complaints is pabrik tahu work. Purpose: The purpose of this study was to determine the association between work fatigue and musculoskeletal disorders in pabrik tahu workers in the Jakarta Timur area. Method: This study uses a quantitative correlation with the Cross-Sectional Study approach. This research has 60 participants who are factory tahu workers in the Jakarta Timur area, the parameters used are the Nordic Body Map (NBM) with the aim of knowing musculoskeletal disorders pain and Fatigue Assessment Scale (FAS) the Industrial to find out work fatigue. Result: The sig (2-tailed) value is obtained, namely p: 0.000, the p-value is less than 0.05, the results of the correlation analysis show that the r value is 0.621. Conclusion: According to the results of the research data, it can be concluded that there is a significant relationship between work fatigue and musculoskeletal disorders in tofu factory workers in East Jakarta.